Case report: recurrent pituitary adenoma has increased load of somatic variants - Peculis, Raitis (BMC Endocr Disord, 2020)
BACKGROUND: Pituitary adenomas (PA) have an increased potential for relapse in one to 5 years after resection. In this study, we investigated the genetic differences in genomic DNA of primary and rapidly recurrent tumours in the same patient to explain the causality mechanisms of PA recurrence. CASE PRESENTATION: The patient was a 69-year-old female with non-functional pituitary macroadenoma with extension into the left cavernous sinus (Knosp grade 2) who underwent craniotomy and partial resection in August 2010. Two years later, the patient had prolonged tumour growth with an essential suprasellar extension (Knosp grade 2), and a second craniotomy with partial tumour resection was performed in September 2012. In both tumours, the KI-67 level was below 1.5%. Exome sequencing via semiconductor sequencing of patient germline DNA and somatic DNA from both tumours was performed. Tmap alignment and Platypus variant calling were performed followed by variant filtering and manual review with IGV software. We observed an increased load of missense variants in the recurrent PA tumour when compared to the original tumour. The number of detected variants increased from ten to 26 and potential clonal expansion of four variants was observed. Additionally, targeted SNP analysis revealed five rare missense SNPs with a potential impact on the function of the encoded proteins. CONCLUSIONS: In this case study, an SNP located in HRAS is the most likely candidate inducing rapid PA progression. The relapsed PA tumour had a higher variation load and fast tumour recurrence in this patient could be caused by clonal expansion of the leftover tumour tissue.